Answer:
DEF is isosceles because we need first to calculate the length of each side.
In order to calculate the length between 2 points like (x1, y1) and (x2, y2), we have to use the next equation:
d = { (x1-x2)^2 + (y1-y2)^2 }^(1/2)
1) In this case the length between D and E is:
DE = { (7-4)^2 + (3-(-3))^2 }^(1/2) = square root of 45
2) In this case the length between E and F is:
EF = { (4-10)^2 + (-3-(-3))^2 }^(1/2) = 6
3) In this case the length between D and F is:
DF = { (7-10)^2 + (3-(-3))^2 }^(1/2) = square root of 45
In conclusion, as we can see DE = DF so this means that the DEF is isosceles.
Explanation: